Identification of The Stages and Weakness of The Student Reasoning in Logical Thinking by The Set - Darmadi, D (Prosiding Konferensi Nasional Penelitian Matematika dan Pembelajarannya, 2019)
The main competence in learning mathematics is to improve the ability of reasoning. To get the competence, the student of the education courses math of Universitas PGRI Madiun compulsory courses logic and set. This paper discusses the stages and the weakness of the student reasoning in the logical thinking with the set. Based on the results of a descriptive research-qualitative study program conducted in mathematics education earned the stages and the weakness of the reasoning of the students in the logical thinking with the set. Stages of reasoning of the students in the logical thinking with the set as a means of visualization are: 1) Connect each set with the premise, 2) Connect both premises and pay attention to the possibilities of possible illicit; and 3) paying attention to both possibilities as the basis for the with draw of the conclusion. Weaknesses of student reasoning in logical thinking with the set as visualization are: 1) Students see problems separately and have not been able to connect with the conclusion or the premise of the set that's been studied; 2) Students can already connect to the problems with the concept of the set but haven't been able to connect between premise; 3) Students can already connect the premise to the concept of set, but less thorough so as to give an answer that is less precise; and 4) Students can already connect to premise by the concept of the set and had a thorough look at all the possibilities so as to provide an answer with precision.